Blogging with smartphones for independent writing practice beyond the EFL classroom - Shaista Rashid; Jocelyn Howard (Universitas Pendidikan Indonesia, 2023)
This study investigated how English as a Foreign Language (EFL) students at a university in Pakistan experienced blogging on their smartphones as a means to gain more extensive autonomous practice writing in English. The blogging was done as a stand-alone activity, independent of the students’ university EFL programme. Using a mixed-methods case study design, data were collected from 23 undergraduate students through interviews, surveys, and reflective written accounts. This paper foregrounded the students’ voices to reveal their attitudes to blogging, their experiences using smartphones for that purpose, and perceived changes in their English writing skills. The findings indicated that many of the participants developed a virtuous cycle, in which their interest and enjoyment of blogging, along with perceived improvements in their ability to communicate in English, contributed to increase both confidence and motivation to write more. The findings also pointed to other worthwhile social and educational outcomes that could be fostered through this type of activity. As a result, the study has implications for teachers and learners in a wide range of EFL contexts, i.e., offering further insights into strategies for harnessing existing digital tools in order to extend students’ opportunities to use the target language, within and beyond formal educational settings.